2023
DOI: 10.1371/journal.pone.0282530
|View full text |Cite
|
Sign up to set email alerts
|

Systematically analysing the acceptability of pig farming systems with different animal welfare levels when considering intra-sustainability trade-offs: Are citizens willing to compromise?

Abstract: In recent years, intensive pig husbandry has been subject to increasing public criticism, including a clear demand for more animal-friendly housing systems in many countries. However, such systems are associated with trade-offs at the expense of other sustainability domains, which challenges implementation and makes prioritization necessary. Overall, research is scarce that systematically analyses citizens’ evaluation of different pig housing systems and associated trade-offs. Given the ongoing transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As the simultaneous consideration of these aspects gives rise to numerous trade-offs, especially regarding animal welfare, we chose the best-worst scaling approach (BWS) to measure citizens' preferences. We consider our results to make a valuable contribution to the field, as previous research differs from our study in several respects: the selection of the aspects investigated, the context in which aspects were evaluated, the methods used to measure importance levels, and the animal species considered (Lusk et al, 2007;Vanhonacker et al, 2007;Sackett et al, 2013;Spooner et al, 2014;Tuyttens et al, 2014;Caracciolo et al, 2016;Cummins et al, 2016;Vanhonacker et al, 2016;Ventura et al, 2016;Verain et al, 2016;Ellison et al, 2017;Grunert et al, 2018;Heise and Theuvsen, 2018;Sonntag et al, 2019a;Faucitano et al, 2022;Schmiess and Lusk, 2022;Schütz et al, 2023). A comparison of the importance levels of the aspects we investigated with previous studies is therefore only possible to a limited extent, which should be kept in mind in the following discussion of the results.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As the simultaneous consideration of these aspects gives rise to numerous trade-offs, especially regarding animal welfare, we chose the best-worst scaling approach (BWS) to measure citizens' preferences. We consider our results to make a valuable contribution to the field, as previous research differs from our study in several respects: the selection of the aspects investigated, the context in which aspects were evaluated, the methods used to measure importance levels, and the animal species considered (Lusk et al, 2007;Vanhonacker et al, 2007;Sackett et al, 2013;Spooner et al, 2014;Tuyttens et al, 2014;Caracciolo et al, 2016;Cummins et al, 2016;Vanhonacker et al, 2016;Ventura et al, 2016;Verain et al, 2016;Ellison et al, 2017;Grunert et al, 2018;Heise and Theuvsen, 2018;Sonntag et al, 2019a;Faucitano et al, 2022;Schmiess and Lusk, 2022;Schütz et al, 2023). A comparison of the importance levels of the aspects we investigated with previous studies is therefore only possible to a limited extent, which should be kept in mind in the following discussion of the results.…”
Section: Discussionmentioning
confidence: 95%
“…Taking farrowing crates for sows and outdoor access for pigs as an example, Sonntag et al (2019a) found that in a trade-off situation, the animal welfare argument (i.e., improved housing conditions) was more convincing than, e.g., economic, technological, or hygienic arguments. In addition, in a recent study by Schütz et al (2023) where different pig housing systems had to be evaluated against the background of emerging trade-offs, citizens were more likely to trade off animal welfare (i.e., housing conditions) against animal or human health than against climate protection or a lower product price.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, studies show that mainly indoor housing systems are criticized due to, e.g. limited space and missing outdoor access (Clark et al, 2016;Weible et al, 2016;K€ uhl et al, 2019;Sch€ utz et al, 2023a). Especially in pig and poultry fattening, however, systems with outdoor access are rather scarce in most countries.…”
Section: Introductionmentioning
confidence: 99%